2007
DOI: 10.1002/jcp.21068
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile of human adipose‐derived stem cells: Expression of angiogenic, hematopoietic, and pro‐inflammatory factors

Abstract: Adipose tissue serves as a source of adipokines and cytokines with both local and systemic actions in health and disease. In this study, we examine the hypothesis that multipotent human adipose-derived stem cells (ASCs), capable of differentiating along the adipocyte, chondrocyte, and osteoblast pathways, contribute to adipose tissue-derived cytokine secretion. Following exposure to basic fibroblast growth factor (bFGF) or epidermal growth factor (EGF), the ASCs significantly increase their secretion of hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
416
4
16

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 579 publications
(447 citation statements)
references
References 41 publications
(56 reference statements)
11
416
4
16
Order By: Relevance
“…It is well known that adipose tissue can promote tissue regeneration through secretion of various cytokines. Previous reports revealed expression of angiogenic cytokines (HGF, VEGF), hematopoietic cytokines (G-CSF, SCF) and pro-inflammatory cytokines (IL-6, LIF, TNFa), [42][43][44] as well as secretion of hypoxia-inducible transcription factor (HIF) in fat-derived stem cells under a hypoxic condition. 45 As HIF-2a has been shown to be upregulated under a hypoxic condition in vitro, hMADS cells might also produce HIF which is one of the upstream molecules of VEGF and angiopoietin-1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that adipose tissue can promote tissue regeneration through secretion of various cytokines. Previous reports revealed expression of angiogenic cytokines (HGF, VEGF), hematopoietic cytokines (G-CSF, SCF) and pro-inflammatory cytokines (IL-6, LIF, TNFa), [42][43][44] as well as secretion of hypoxia-inducible transcription factor (HIF) in fat-derived stem cells under a hypoxic condition. 45 As HIF-2a has been shown to be upregulated under a hypoxic condition in vitro, hMADS cells might also produce HIF which is one of the upstream molecules of VEGF and angiopoietin-1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, pADSCs and pPiPSC-DCs were both found to repress the proliferation of mouse PBMCs. Multiple secretory factors, such as transforming growth factor b (TGFb), prostaglandin E 2 (PGE 2 ), interleukin 6 (IL6), and M-CSF (Cui et al 2007, Kilroy et al 2007, have been reported to be involved in this process. Moreover, MSCs can suppress the proliferation and transformation of immunocytes, which requires galectin 1 to regulate the secretion of TNFa, IFNg, and IL2 (Gieseke et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The primary human cell products should meet quality control/quality assurance criteria outlined by national and and differentiation in vitro of co-cultured human umbilical cord-derived hematopoietic progenitors. 34,35 Immunomodulatory Role of ASC In recent years, considerable attention has focused on the paracrine and immunomodulatory mechanism of SVF cell and ASC reparative function. Multiple independent studies have used the mixed lymphocyte reaction (MLR) as an in vitro approach.…”
Section: Regulatory Environment For Stromal/stem Cellsmentioning
confidence: 99%